1991
DOI: 10.52321/geolbalc.21.4.3
|View full text |Cite
|
Sign up to set email alerts
|

A geodynamic model of the Alpine magmatism in Bulgaria

Abstract: The territory of Bulgaria covers part of the active continental margin of the Eurasian plate. Several first-order tectonic units may be distmguished: Moesian platform, paraautochthonous margin of the platform, zone of Mid-Mesozoic collage units, Late Cretaceous island-arc system and a system of Cenozoic collisional and post-collisional grabens. The Alpine magmatism is genetically related to the evolution of the Eurasian margin and the Tethyan ocean south of it. The earliest Alpine magmatic activity is represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…The Triassic volcanic activity described above is the earliest sign of Alpine magmatism in Bulgaria related to the embryonal rifting of the Moesian platform (Rneo, liaxneaa, 1980;Haqeo, 1980;Boyanov et al, 1989;Dabovski et al, 1991). The West Fore-Balkan rift zone is situated along the border of the Moesian platform with the West Balkan accreted block.…”
Section: Tectonicsmentioning
confidence: 95%
“…The Triassic volcanic activity described above is the earliest sign of Alpine magmatism in Bulgaria related to the embryonal rifting of the Moesian platform (Rneo, liaxneaa, 1980;Haqeo, 1980;Boyanov et al, 1989;Dabovski et al, 1991). The West Fore-Balkan rift zone is situated along the border of the Moesian platform with the West Balkan accreted block.…”
Section: Tectonicsmentioning
confidence: 95%
“…The present knowledge about the Alpine igneous activity in SW Bulgaria gives no grounds to relate this activity to a special Kraishtide zone. Harkovska et al (1989Harkovska et al ( , 2003 and Dabovski et al (1991) demonstrated that both the Late Cretaceous and the Palaeogene igneous activities in the Morava-Rhodope zone Zagorchev et al (2006) are related to two large arcs roughly parallel to the boundaries of this zone. ZagorÄŤev, Moorbath (1987) have demonstrated an increasing tendency in the values of the initial strontium isotopic ratio ( 87 Sr/ 86 Sr) 0 from the Srednogorie zone towards South related to the thinning of the crust with crustal necking and formation of magmas in the upper mantle of the Srednogorie, and upwelling of the melting isotherm in the Rhodope (Northern Pirin included) region with formation of anatectic granitoid magmas with crustal signature.…”
Section: Alpine Igneous Activitymentioning
confidence: 99%
“…However, the latest Eocene -Early Oligocene ingression that formed the Padesh-Piyanets shallow gulf is clearly oblique to the "Kraishtides", penetrating from the Southwest (Tikvesh and Ovchepolje) to Northest. Observations over a wider region show that both the Palaeogene (Eocene -Oligocene) sedimentation and volcanism (Harkovska et al, 1989;Dabovski et al, 1991) were located within a large arc South of the Srednogorie zone, and related to the extensional collapse of the Srednogorie Late Cretaceous orogen, and mostly to the collapse of the "plateau" situated to the South (Morava-Rhodope zone - Dabovski et al, 2002).…”
Section: Alpine Sedimentationmentioning
confidence: 99%
“…Alluvial conglomerates with strongly varying thickness and fragment size have been formed followed by a lake (or even a shallow sea gulf) with periodic influx of coarser and finer-grained material (Souhostrel Formation). The erosion of the Palaeogene lateritic weathering crust and the intensification of the block movements in Late Eocene times Jed to the deposition of the polymictic conglomerates of the Komatinitsa Formation, and especially, to the coarse gravity-induced breccia ("olistostromes" - MocKoB-CKH, 1987, 1991 and fault-bound coarse conglomerate of the Logodash Formation interfingering with sandstone and shale in the deeper lacustrine parts of the Piyanets basin (3aropt.feB, ITonos, 1968). The active synsedimentary normal faulting occurred along the Lisiya fault zone, with a considerable subsidence and deposition of more than 700 m of sediments within the western block.…”
Section: Palaeogene Tectonicsmentioning
confidence: 99%